Mutation in ITCH gene can cause syndromic multisystem autoimmune disease with acute liver failure - Kleine-Eggebrecht, Nicola Alexandra; Staufner, Christian (Pediatrics, 2019)
Pediatric intractable autoimmune hepatitis is rare and may be responsible for acute liver failure. Mutations in the itchy E3 ubiquitin protein ligase (ITCH) gene (located on chromosome 20q11.22) can lead to a deficiency of the encoded protein, resulting in increased T-cell activity with lack of immune tolerance and manifestation of a complex systemic autoimmune disease. A 1-year-old girl of consanguineous parents received a liver transplant (LT) because of acute liver failure attributed to a drug-induced hypereosinophilic syndrome with positive liver-kidney-mikrosome-2 antibodies. Notable findings were syndromic features, dystrophy, short stature, psychomotor retardation, and muscular hypotonia. Later, we saw corticosteroid-sensitive rejections as well as a systemic autoimmune disease with detection of specific antibodies (de novo autoimmune hepatitis, thyroiditis with exophthalmos, diabetes mellitus type 1, and immune neutropenia). Histologically, liver cirrhosis with lobular inflammatory infiltrates, giant-cell hepatitis, and ductopenia was verified in chronic cholestasis. Shortly after a second LT, a comparable liver histology could be detected, and viral, bacterial, and mycotic infections deteriorated the general health condition. Because of refractory pancytopenia related to portal hypertension and hypersplenism, a posttransplant lymphoproliferative disorder was excluded. One year after the second LT, epidural and subdural bleeding occurred. Three months afterward, the girl died of sepsis. Postmortem, whole-exome sequencing revealed a homozygous mutation in the ITCH gene. A biallelic mutation in ITCH can cause a severe syndromic multisystem autoimmune disease with the above phenotypic characteristics and acute liver failure because of autoimmune hepatitis. This case reveals the importance of ubiquitin pathways for regulation of the immune system.